Trust and Reciprocity: A Cross-Cultural Study - Zhenxia, Wu (2009)
I compared the results of trust game and survey questions under an individual versus group setting for China and UK using a mixed sample with randomly selected students and non-students. Both Chinese and British people intend to invest into the group without considering cultural effects. But British individual and groups are embedded with more trust and trustworthiness but are more sensitive to cultural differences. Both Chinese and British participants intend to trust other groups from their own country more than they trust groups from other nations. Lots of attitudinal factors and personal characteristics have been test as well. General attitude toward trust, trusting experience in the past, educational level, and income level have significant influence on the investment decision. However, significant cultural effect was only detected on past trusting experience and income level.